Its Role In Self Regulated Learning Case Study On Junior High School Students Of It Madani Islamic School - Rahmaniyah Madwa Ista; Tarmidi Tarmidi; Fasti Rola (Eduvest - Journal of Universal Studies, 2024)
Adolescence is a critical period for student education, where students are in the transition period of childhood to adulthood that undergoes changes in their biological, cognitive and socio-emotional conditions. Based on the stage of development, junior high school students should be able to have responsibility in learning, students are able to manage themselves in their way of learning. The focus of this study aims to examine the role of personality type (based on the STIFIn method) and school climate on the self-regulated learning of SMP IT Madani Islamic School students. Sampling in this study used a total sampling involving 300 students. Data collection uses personality type data (based on the STFIn method), school climate scale and self-regulated learning scale. The data analysis technique used in this study is multiple regression analysis. The results showed that STIFIn personality type and school climate played a significant role in self-regulated learning with a value of F = 44,707 and a value of p<.05. Personality type and school climate made an effective contribution of 26.2% to self-regulated learning.